Evaluation of MUC1 and P53 expressions in noninvasive papillary urothelial neoplasms of bladder, their relationship with tumor grade and role in the differential diagnosis - Esin Kaymaz; Elif Ozer; Hatice Unverdi; Sema Hucumenoglu (Wolters Kluwer Medknow Publications, 2017)
Purpose: The aim of this study was to investigate the usability of MUC1 and p53 for differential diagnosis of noninvasive papillary urothelial neoplasias, especially for distinguishing papillary urothelial neoplasm of low malignant potential (PUNLMP) from low-grade papillary urothelial carcinoma (LGPUC) when the histologic signs are not obvious. Materials and Methods: Seventeen biopsy specimens of the patients with PUNLMP, 20 with LGPUC and 13 with high-grade papillary urothelial carcinoma (HGPUC) were stained for MUC1 and p53 protein by immunohistochemical methods. Histological grading was performed according to an algorithm, which allows histological parameters used in 2004 WHO/ISUP 1998. Results: We had obvious statistical difference for aberrant expression pattern of MUC1 between PUNLMP and LGPUC-HGPUC (P = 0.007). Positivity of MUC1 expression in cytoplasm of basal cells was more observed in HGPUC and LGPUC, whereas PUNLMP was more often showing apical and superficial positivity of MUC1 expression (P = 0.001 and 0.011). Nuclear p53 protein in HGPUC was obviously more frequent than that in LGPUC and PUNLMP (P < 0.001). Measures showed statistical difference among aberrant MUC1 expression, p53 overexpression, and tumor grade (P < 0.001). Conclusions: MUC1 and p53 may be helpful immunohistochemical markers for distinguishing PUNLMP from LGPUC and HGPUC, when the histologic signs are not obvious.